Unifid protocol for anxiety disorders in two cities of Mexico measuring gamma activity: Study protocol for a randomized controlled trial - Dominguez-Rodriguez, Alejandro; Avitia, Graciela Cristina; Chavez-Valdez, Sarah Margarita; Vlencia-Espinoza, Laura (2020)
Background: The Unifid Protocol for Emotional Disorders (UP) for emotional regulation manifests effective results in a broad range of mental disorders. The UP effiacy was tested in several countries, but it has not been tested within Mexican population. It is crucial to do more research and implement effective protocols to intervene Mexican population with Anxiety Disorders (AD). Objective: This study aims to examine and describe the research procedures and treatment interventions of the UP in a Randomized Controlled Trial (RCT), to approach and treat AD in patients in 2 Mexican borderland cities, by applying the UP and an Electroencephalogram (EGG) neuro screening. Methods: The enrolled patients will be randomized in a two-arm control trial with repeated measures, comprising between 18 and 60 years, that were diagnosed with an AD, and low scored in depression symptoms and suicidal ideation. The study will comprise of two conditions: an intervention group clinical trial with the UP or a waiting list control. The primary outcome measures will be applied on AD quantitative self-reports and a gamma activity by EGG before and after the intervention and in follow-ups of 3 and 6 months. The participants in the waiting list group, will receive the treatment after the trial fist group completes the treatment. Conclusions: Processes and outcomes of this project, will provide evidence in order to apply the UP in a broader population with AD and other mental disorders also covered by this protocol, such as depression and borderline personality disorder in a broader Mexican population, a country that suffers with a major health issue with an increasing rate of mental disorders and scarce psychological and health coverage.